Formy pomocy pastoralnej studentom pochodzących z rodzin z problemem alkoholowym - Polok, Grzegorz (Studia Pastoralne, 2026)
A group of adults classified as Adult Children of Alcoholics is growing in our country. Also students belong to this group which causes significant pastoral challenge for academic chaplaincy. Students – Adult Children of Alcoholics – that undergo therapy should obtain special support by community of academic chaplaincy. First of all, in the community, they should experience God’s love and anchor their life changes in God’s unconditional love towards them. This experience of meeting God should be achieved by Eucharist, sacrament of penance and reconciliation and sacrament of the sick. Joint and individual reflection upon the Bible, as well as prayers within the community of academic chaplaincy, should also become a way of discovering unconditional love of God and His care about every man. Academic chaplaincy, offering community support to Adult Children of Alcoholics students, should also organize professional psychological and therapeutical support for them.